Biochar as a sorbent for emerging contaminants enables improvements in waste management and sustainable resource use. (10th February 2019) - Li, Longcheng; Zou, Dongsheng; Xiao, Zhihua; Zeng, Xinyi; Zhang, Liqing; Jiang, Longbo; Wang, Andong; Ge, Dabing; Zhang, Guolin; Liu, Fen
Abstract: Emerging contaminants have recently been recognized as new and significant water pollutants and gained great of concerns because of their considerable effects on ecosystems and human health. Current conventional wastewater treatment technologies are not efficient at removing these trace contaminants; novel and lower cost approaches are required. Biochar is well-known as an effective adsorbent for the removal of complex inorganic contaminants and organic contaminants from water. This review provides a summary of recent research on the underlying mechanisms controlling the presence of emerging contaminants in water, as well as their removal and the environmental treatment of soil by biochar. A range of information is also presented regarding the application of this resource; it is clear that a variety of cheap, efficient, modified, and composite biochar that is able to remove emerging contaminants will be required to further advance research progress. Highlights: Outline the major hazards, sources and pathways of ECs. Research techniques and adsorption mechanisms of biochar to remove ECs. Review and analyse the current application of biochar to remove ECs. The current situation and future risks that affect this process.